If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c = 6 + 2c Solving 3c = 6 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 3c + -2c = 6 + 2c + -2c Combine like terms: 3c + -2c = 1c 1c = 6 + 2c + -2c Combine like terms: 2c + -2c = 0 1c = 6 + 0 1c = 6 Divide each side by '1'. c = 6 Simplifying c = 6
| 15.25d+9.50d+40=213.25 | | 3(2-0.9h)+(-1.3-4)= | | 1=0.1408450704b-1(0-b)(0-7.1) | | -10x+5x+40=90 | | (48-18)+5x=48 | | 0.20(y-9)+0.10y=0.14y-0.05(20) | | -144=11x | | 8x-5=2x-4 | | 8(-7-8n)=16+8n | | Y-k= | | 6x+18=4x+28 | | Y+4-2x=0 | | X^2-2x+3x+108=108 | | 4t^2-17t-1=0 | | .5y+.25(y+16)=4+.75y | | -13=-2.5x-3 | | (3x+7)+(3x+6)+(3x)=(3x)+(3x)+(4x+4) | | 2n+5y+5n-6y-2k= | | 0.50x+0.15(50)=25.5 | | X^2+112=16x+131 | | (5x+4)+54=180 | | -7x^2+6x-8=-4-4x | | -6(-8-7x)+5=-37-3x | | 3m+2n+5m+4n= | | 3t+1=6t-9 | | 1.1+-15x+3x=15x+-2+4 | | 4x=2(x+1)+3(x+1) | | z+2y=114x | | 2(4x-3)=-26+4x | | -3+9z+2-7z= | | 100x=5x-1 | | 11+4j=-5 |